Ureteroscopy in Pregnant Women for Ureteral Stone - Travassos, Marcelo [UNESP]; Amselem, Isaac; Sa Filho, Newton; Miguel, Marshall; Sakai, Americo; Consolmagno, Horacio; Nogueira, Marcos; Fugita, Oscar Eduardo Hidetoshi [UNESP] (Mary Ann Liebert, Inc., 2009)
Introduction: The occurrence of urolithiasis in pregnancy represents a challenge in both diagnosis and treatment of this condition, because it presents risks not only to the mother but also to the fetus. Surgical treatment may be indicated for patients with infection, persistent pain, and obstruction of a solitary kidney. We present our experience on the management of pregnant patients with ureteral calculi and a review of the literature.Materials and Methods: The charts of 19 pregnant patients with obstructive ureteral calculi were retrospectively reviewed. Gestational age ranged from 13 to 33 weeks. In all patients, ureteral stone was diagnosed on abdominal ultrasound. In regard to localization, 15 calculi were in the distal ureter, 3 in the proximal ureter, and 1 in the interior of an ureterocele. Calculi size ranged from 6 to 10 mm (mean, 8 mm). The following criteria were used to indicate ureteroscopy: persistent pain with no improvement after clinical treatment, increase in renal dilation, or presence of uterine contractions. Nine patients (47.3%) were submitted to ureteroscopy. All calculi (100%) were removed with a stone basket extractor under continuous endoscopic vision. None of the calculi demanded the use of a lithotriptor.Results: Nine patients (47.3%) treated with clinical measurements presented no obstetric complications and spontaneous elimination of the calculi. Nine patients (47.3%) submitted to ureteroscopy had no surgical complications. There was remission of pain in all cases after ureteroscopy and ureteral catheter placement.Conclusion: The diagnosis and treatment of ureteral lithiasis in pregnant women present potential risks for the fetus and the mother. Conservative management is the first option, but ureteroscopy may be performed with safety and high success rates.